Integrating Blended Teaching in English Learning: Enhancing Communication and Cognitive Engagement in Sports Education Post-Epidemic - Lu Sun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The rapid advancement of digital technologies has transformed education, providing opportunities for online teaching to overcome traditional time and space limitations and enhance resource sharing. However, in the post COVID-19 era, traditional online teaching approaches alone have proven insufficient for fostering active engagement and cognitive development. To address this, integrating the flexibility of online teaching with the structure of offline methods has become crucial for curriculum reform, particularly in sports education, where communication, motivation, and interaction play critical roles. the school has emphasized the reform of teaching methodologies by adopting a blended teaching approach that combines offline and online learning. This approach ensures comprehensive planning and the development of management systems, mechanisms, and standards tailored to the unique demands of sports education. In the context of English learning for sports students, blended teaching methods are applied during the initial, implementation, and post-class stages to enhance language skills while promoting team communication and cognitive engagement. This integration not only supports language proficiency but also cultivates psychological resilience and collaborative abilities essential for success in sports education and practice.